DIFFERENCES IN THE USE OF ROLE PLAYING METHODS AND LECTURE METHODS ON THEMATIC LEARNING OUTCOMES OF CLASS V SDN 9 BANYUWANGI - Putri Faradila Dianita (Journal of Education Technology and Inovation, 2022)
One of the efforts to improve the quality of education is through the introduction of contemporary curriculum development and role playing methods which are very suitable for elementary school thematic learners. In learning activities that use role play, the teacher can combine several subjects in one activity. This of course will make it easier and save the teacher's time to convey learning material. The purpose of this research is to find out whether the use of the role playing method has an effect on thematic learning outcomes. The research was conducted in class V of elementary school with a total of 70 students. Data collection techniques used questionnaires, tests and documentation. The data analysis technique uses multiple linear regression to test learning outcomes, using individual sample t-tests. The results showed that the t-test analysis of descriptive statistics on learning outcomes showed a significant difference between the average students who were treated with an average of 83.43 using the role playing method. This means that the role play method is very possible. While increasing student learning outcomes, students who were treated with the lecture method averaged 70.29. This means that the application of the lecture method has not been effective in improving student learning outcomes. In the t-test analysis using SPSS 23.00 the coefficient is less than 0.05 so the tcount is 12.179 which is significant. Furthermore, it can be said that there is a positive influence in the use of role playing learning on thematic learning outcomes of elementary school students